A fundamental distinction in early neural processing of implicit social interpretation in schizophrenia and bipolar disorder - Madeira, N (2022)
Background: Social cognition impairment is a key phenomenon in serious mental disorders such as schizophrenia (SCZ) and bipolar disorder (BPD). Although genetic and neurobiological studies have suggested common neural correlates, here we hypothesized that a fundamental dissociation of social processing occurs at an early level in these conditions. Methods: Based on the hypothesis that key structures in the social brain, namely the temporoparietal junction, should present distinctive features in SCZ and BPD during low-level social judgment, we conducted a case-control study in SCZ (n = 20) and BPD (n = 20) patients and controls (n = 20), using task-based fMRI during a Theory of Mind (ToM) visual paradigm leading to interpretation of social meaning based on simple geometric figures. Results: We found opposite neural responses in two core ToM regions: SCZ patients showed social content-related deactivation (relative to controls and BPD) of the right supramarginal gyrus, while the opposite pattern was found in BPD; reverse patterns, relative to controls and SCZ, were found in the left posterior superior temporal gyrus, a region involved in inferring other's intentions. Receiver-operating-characteristic curve analysis showed 88% accuracy in discriminating the two clinical groups based on these neural responses. Conclusions: These contrasting activation patterns of the temporoparietal junction in SCZ and BPD represent mechanistic differences of social cognitive dysfunction that may be explored as biomarkers or therapeutic targets.